Assessing Body Dysmorphic Disorder Prevalence among Patients Seeking Cosmetic Dermatology Procedures in a Tertiary Care Hospital - Singh, Neha; Anupama YG; Tumbal, Namita A; Dadapeer HJ (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Body Dysmorphic Disorder (BDD) is a psychiatric condition, with the primary symptom being an impairing preoccupation with a non-existent or slight defect in appearance, leading to seeking multiple cosmetic procedures. It is often difficult to diagnose, causing a lot of suffering, and is more prevalent in dermatology patients. There are few reports on the prevalence of BDD in the Indian population. Objectives: To determine the prevalence of BDD among patients seeking cosmetic dermatologic procedures, to analyse the relationship between dermatological and sociodemographic variables and possible cases of BDD, and to provide data on the phenomenology of compulsive behaviours associated with BDD. Materials and Methods: A total of 150 patients seeking cosmetic procedures in Shimoga Institute of Medical Sciences, Shivamogga were included in the study. Body Dysmorphic Disorder Questionnaire- Dermatology Version was used to screen the possible cases of BDD. Results: In our sample, we obtained a prevalence for BDD of 11.3% (95% CI: 6.05% -16.61%). The median age in the BDD group was 28 (26,33) which was slightly lower compared to the non-BDD group. 70.6% of BDD patients were females. 76.5% of BDD patients had a history of previous treatments. This was high compared to non BDD group and is statistically significant. 47.1% of BDD patients had facial pigmentation as their primary concern. The most frequent compulsive behaviour in BDD patients was in comparison with others (47.1%). Conclusion: BDD is relatively common in a dermatologic setting, especially among patients seeking cosmetic treatments. Dermatologists should be aware of its clinical characteristic of BDD to avoid unnecessary procedures and refer these patients to mental health professionals.